Ethnicity and religion: the rol of the religion in the process of indigenous identity reconstruction (2009)
The text analyzes about evolution and that the recognition of the native in Colombia and other countries of Latin America has been right; therefore to investigate by the concept of cultural identity, and the featuring of the religion in the construction o